Insulin-Like Growth Factor-I Plays a Pathogenetic Role in Diabetic Retinopathy - Poulaki, Vassiliki (American Society for Investigative Pathology, 2004)
Diabetic retinopathy is a leading cause of blindness in the Western world. Aberrant intercellular adhesion molecule-1 expression and leukocyte adhesion have been implicated in its pathogenesis, raising the possibility of an underlying chronic inflammatory mechanism. In the current study, the role of insulin-like growth factor (IGF)-I in these processes was investigated. We found that systemic inhibition of IGF-I signaling with a receptor-neutralizing antibody, or with inhibitors of PI-3 kinase (PI-3K), c-Jun kinase (JNK), or Akt, suppressed retinal Akt, JNK, HIF-1α, nuclear factor (NF)-κB, and AP-1 activity, vascular endothelial growth factor (VEGF) expression, as well as intercellular adhesion molecule-1 levels, leukostasis, and blood-retinal barrier breakdown, in a relevant animal model. Intravitreous administration of IGF-I increased retinal Akt, JNK, HIF-1α, NF-κB, and AP-1 activity, and VEGF levels. IGF-I stimulated VEGF promoter activity in vitro, mainly via HIF-1α, and secondarily via NF-κB and AP-1. In conclusion, IGF-I participates in the pathophysiology of diabetic retinopathy by inducing retinal VEGF expression via PI-3K/Akt, HIF-1α, NF-κB, and secondarily, JNK/AP-1 activation. Taken together, these in vitro and in vivo signaling studies thus identify potential targets for pharmacological intervention to preserve vision in patients with diabetes.